Hostile attributions in bipolar disorder and schizophrenia contribute to poor social functioning. (31st January 2015) - Lahera, G.; Herrera, S.; Reinares, M.; Benito, A.; Rullas, M.; González‐Cases, J.; Vieta, E.
<x xml:space="preserve">Abstract</x> Objective To compare the profile of attributional style of a group of out‐patients with bipolar disorder (BD) and schizophrenia (SZ), and a group of healthy controls – along with other social cognition domains – such as emotion recognition and theory of mind (ToM). Method A total of 46 out‐patients diagnosed with BD, 49 with SZ, and 50 healthy controls were assessed in attributional style (Ambiguous Intentions Hostility Questionnaire), facial emotion recognition (FEIT, FEDT, ER‐40), and ToM (Hinting Task). Symptomatology, clinical variables and global functioning were also collected. Results Both groups with SZ and BD showed hostile social cognitive biases, compared with the control group. Patients with BD also showed a capacity for emotional recognition similar to those with SZ and worse than control subjects. In contrast, patients with SZ showed poorer ToM. Subthreshold depressive symptoms and an attributional style toward hostility appeared as the factors with a strongest association to global functioning in BD. In SZ, PANSS score and a tendency to aggressiveness were the most relevant factors. Conclusion Attributional style (along with other domains of social cognition) is altered in out‐patients with BD and SZ. The presence of residual symptoms and a hostile social cognitive bias may contribute to the functional impairment of both groups.